Spatial Structure of The Leisure Zone in The Pangururan District Urban Waterfront - Erni Triska (International Journal of Architecture and Urbanism, 2021)
Pangururan is a district in Samosir regency, north sumatera province, Indonesia. Pangururan also the capital city of samosir regency and pangururan district capital is Pasar Pangururan. In Indonesian population census 2020, Pangururan has 34.209 population. Samosir regency residents mostly Batak Toba tribe and some are Batak Angkola, Batak Simalungun, Batak Karo tribe and immigrant from Java, Minangkabau, and Nias that are mostly resides in the capital city. Residents of Pangururan commonly farming for living. And for the residents who lived near the shore of the lake are mostly fisherman. Now, Pangururan waterfront area is included in an area arrangement project called Waterfront City Pangururan (WCP). WCP is a part from Program Pembangunan Pariwisata Terintegrasi dan Berkelanjutan (P3TB) for Lake Toba destinantion of tourism and promoting Lake Toba as KSPN. There are many leisure zones in Pangururan District Urban Waterfront that changes the spatial structure of Pangururan. This research uses qualitative method. The aim of this research is to find identification from the effect of tourism toward pattern and spatial structure in Pangururan Waterfront Area is needed.